2021
DOI: 10.1111/jocn.15797
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of organisational justice, psychological capital and professional identity with job burnout among Chinese nurses: A cross‐sectional study

Abstract: Aims and objectives: The present study was aimed at describing the status of job burnout and exploring the mediating roles of psychological capital and professional identity on the association between organisational justice and job burnout.Background: With the shortage of nurses all over the world, nurses' job burnout has become the focus of studies in recent years. However, limited published research has examined the mediating roles of psychological capital and professional identity on the association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 39 publications
4
43
2
Order By: Relevance
“…This current study found that perceived organisational justice is significantly positively correlated with professional identity, which is consistent with previous studies (Ren et al, 2021). As a key element in an organisation, employees' perception of justice in the organisational environment related to their rights and interests will affect their psychological states and actions related to organisational performance (Liu et al, 2003).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This current study found that perceived organisational justice is significantly positively correlated with professional identity, which is consistent with previous studies (Ren et al, 2021). As a key element in an organisation, employees' perception of justice in the organisational environment related to their rights and interests will affect their psychological states and actions related to organisational performance (Liu et al, 2003).…”
Section: Discussionsupporting
confidence: 93%
“…No literature was found to report the relationship among nurses' organisational justice, professional identity, emotional labour and job performance. There was some research (Baka, 2018; Levin et al, 2020; Ren et al, 2021) that examined the relationships between perceived organisational justice and job performance, professional identity and job performance and perceived organisational justice and professional identity. The results of this study are consistent with these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy, defined as people’s self-confidence in facing great challenges and breaking through the difficulties, may directly affect one’s professional identity ( Bandura, 1997 ; Xiong et al, 2020 ). Low self-efficacy may cause burnout and low job satisfaction ( Bulfone et al, 2016 ; Yao et al, 2018 ), resulting in a low professional identity level ( Ren et al, 2021 ). Furthermore, self-efficacy was positively correlated with professional identity in the previous studies ( Qiu et al, 2019 ; Shen et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…70 Adequate goodness of fit existed when χ 2 /df was less than 5, CFI, NFI and TLI were above 0.9, and RMSEA was less than 0.08. 71,72 Logistic regression was performed to investigate the distribution of socio-demographic characteristics for contracted patients. Multiple linear regression and Hayes's PROCESS macro (Model 59) were conducted to construct the analyses of moderated mediation.…”
Section: | Statistical Analysismentioning
confidence: 99%